KESALAHAN PENGGUNAAN KALA DALAM KARANGAN MAHASISWA ANGKATAN 2016 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Ramadona Ramadona; Mangatur Sinaga; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research the purpose of this research was to describe and eksplaint the cause of tense in students essay. This research was conducted in Japanese Language Education department Teacher is Training and Education Faculty of the Riau University. This research is a qualitative research with descriptive method. The main data sources from fifteen of essay 2016 grade students of Japanese Language Education Study Program University of Riau’s students. The data was obtained by documentatioan technique. The analysis results show that the mistake made by interlingual transfers and intralingual transfers. Interlingual transfers is error caused by the influence of Indonesia language on the target language and intralingual transfers is error caused by the difficulty of the target language system or internal factors the target language.Key Words: Error, mistake, tenses, essay, interlingual transfers, intralingual transfers